2004
DOI: 10.1073/pnas.0400913101
|View full text |Cite
|
Sign up to set email alerts
|

Gene discovery in genetically labeled single dopaminergic neurons of the retina

Abstract: In the retina, dopamine plays a central role in neural adaptation to light. Progress in the study of dopaminergic amacrine (DA) cells has been limited because they are very few (450 in each mouse retina, 0.005% of retinal neurons). Here, we applied transgenic technology, single-cell global mRNA amplification, and cDNA microarray screening to identify transcripts present in DA cells. To profile gene expression in single neurons, we developed a method (SMART7) that combines a PCR-based initital step (switching m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 40 publications
3
49
0
Order By: Relevance
“…This is consistent with accumulating reports indicating that SMART-amplification can maintain relative expression levels of low and abundant cellular mRNA/cDNA (Herrler, 2000;Chen et al, 2001;Zhumabayeva et al, 2001Zhumabayeva et al, , 2004Seth et al, 2003;Wang et al, 2003;Gustincich et al, 2004;Rihl et al, 2004;Wellenreuther et al, 2004). In fact, our previous studies demonstrated that frequencies of Vβ families in SMART-derived cDNA were similar to those in conventional cDNA or anchored PCR-enriched cDNA when using a semi-quantitative method (Chen et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with accumulating reports indicating that SMART-amplification can maintain relative expression levels of low and abundant cellular mRNA/cDNA (Herrler, 2000;Chen et al, 2001;Zhumabayeva et al, 2001Zhumabayeva et al, , 2004Seth et al, 2003;Wang et al, 2003;Gustincich et al, 2004;Rihl et al, 2004;Wellenreuther et al, 2004). In fact, our previous studies demonstrated that frequencies of Vβ families in SMART-derived cDNA were similar to those in conventional cDNA or anchored PCR-enriched cDNA when using a semi-quantitative method (Chen et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…It would therefore be useful to be able to enrich limited amounts of mRNA/cDNA and employ the enriched cDNA for real-time quantitation of antigen-specific T cell clones in the limited amounts of clinical specimens. The SMART-based amplification technique has proven to be a useful method to enrich a limited amount of mRNA/cDNA for a large-scale quantitation of gene expression or arrays (Herrler, 2000;Chen et al, 2001;Zhumabayeva et al, 2001Zhumabayeva et al, , 2004Seth et al, 2003;Wang et al, 2003;Gustincich et al, 2004;Rihl et al, 2004;Wellenreuther et al, 2004). However, SMART-based real-time quantitation technology has not been validated for its utility in quantitating or measuring frequencies of antigen-specific T cell clones in small amounts of PBMC or tissue.…”
Section: Validation Of Smart-based Real-time Quantitative Pcr For Quamentioning
confidence: 99%
See 1 more Smart Citation
“…In rat retinas, dopamine release is lowest at night and highest during the day, even in constant darkness and in animals without photoreceptors, adult RCS/N-rdy rats homozygous for the rdy (retinal dystrophy) allele of photoreceptors (Doyle et al, 2002b). These rhythms might be maintained by melatonin release from the pineal gland (Doyle et al, 2002a) or by endogenous oscillations in the dopaminergic amacrine cells themselves (Gustincich et al, 2004;Witkovsky, 2004), but histaminergic retinopetal axons, which remained intact in these experiments, might also play an important role. Although HR1 receptors typically mediate excitatory effects, there are also known inhibitory effects (Brown et al, 2001).…”
Section: Hr1 In Rat Retinasmentioning
confidence: 99%
“…To describe the precise anatomy of DA cells and record from them physiologically, we generated a line of transgenic mice in which dopaminergic neurons were labelled genetically by human placental alkaline phosphatase [11], developed a technique for single cell mRNA amplification and used cDNA screening to identify the transcripts that are components of DA cells' expression profile [12].…”
Section: Introductionmentioning
confidence: 99%